2004
DOI: 10.1111/j.1469-8137.2004.01035.x
|View full text |Cite
|
Sign up to set email alerts
|

Do phosphorus nutrition and iron plaque alter arsenate (As) uptake by rice seedlings in hydroponic culture?

Abstract: Summary• A hydroponic experiment was conducted to investigate the effect of phosphorus (P) nutrition and iron plaque on root surfaces on arsenate uptake by, and translocation within, the seedlings of three cultivars of rice ( Oryza sativa ).• Supply of 0.5 mg As l − 1 had no significant effects on dry weights of shoots or roots, but resulted in elevated concentrations of As in tissues, particularly in roots. Rice roots appeared reddish after 24 h in -P solution (without P), indicating the formation of iron pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
157
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(169 citation statements)
references
References 38 publications
9
157
1
Order By: Relevance
“…The corresponding ear samples were washed with deionized water, dried at 70°C for 48 h, and then separated into husk and rice grain using a rice sheller. Iron plaque was extracted from fresh root surfaces using dithionite-citrate-bicarbonate (DCB) solution containing 0.03 M sodium citrate and 0.125 M sodium bicarbonate, with the addition of 0.02 g sodium dithionite per milliliter (Taylor and Crowder 1983;Liu et al 2004). The root sample per cluster was immersed in DCB solution (200 ml) at 25°C for 60 min, and then rinsed three times with deionized water.…”
Section: Sampling and Chemical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The corresponding ear samples were washed with deionized water, dried at 70°C for 48 h, and then separated into husk and rice grain using a rice sheller. Iron plaque was extracted from fresh root surfaces using dithionite-citrate-bicarbonate (DCB) solution containing 0.03 M sodium citrate and 0.125 M sodium bicarbonate, with the addition of 0.02 g sodium dithionite per milliliter (Taylor and Crowder 1983;Liu et al 2004). The root sample per cluster was immersed in DCB solution (200 ml) at 25°C for 60 min, and then rinsed three times with deionized water.…”
Section: Sampling and Chemical Analysismentioning
confidence: 99%
“…Rinse water was poured into the DCB extracts and the total volume was made up to 250 ml with deionized water. The final solution was passed through a 0.45-μm nylon filter and refrigerated at 2°C until analysis (Liu et al 2004). After extraction by DCB solution, fresh roots were oven-dried at 70°C for 48 h.…”
Section: Sampling and Chemical Analysismentioning
confidence: 99%
“…Because As-colloids might contribute to limit availability and bioavailability of this toxic element in waters, the evidence that a large amount of As(III) is not linked to Fe(II)-colloids but is present in dissolved ''solute'' form is of relevance when studying As mobility and transfer in soil/water/plant systems under anoxic conditions such as in flooded paddy fields (Liu et al, 2004;Chen et al, 2005;Bravin et al, 2008;Garnier et al, 2010).…”
Section: Table 2bmentioning
confidence: 99%
“…Indeed, in the case of rice, As complexation by colloidal particles may significantly reduce its bioavailability for the plant by competitive effects between colloidal reactive sites and Asspecific sites (or Fe plaque) on the cell membrane of roots (Liu et al, 2004;Guo et al, 2005). Therefore, in the present paper, the leading role of such colloids was investigated through the occurrence of colloidal species and the impact of components such as Fe, Mn, PO 3À 4 and SiO 4À 4 on colloid formation.…”
Section: Introductionmentioning
confidence: 97%
“…An additional complication with rice is that, in the field, roots are usually coated with iron plaque due to the release of oxygen or oxidants into the rhizosphere, which promotes the oxidation of ferrous to ferric iron, the latter being precipitated on the root surface (Bacha and Hossner, 1977;Chen et al, 1980;Liu et al, 2004Liu et al, , 2005. It has been shown that the presence of iron plaque interferes with the conventional PeAs interactions in soil-plant systems (Chen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%